Colocación y relaciones de trabajo. Niños, niñas y jóvenes en el centro y sur de la Provincia de Buenos Aires - de Paz Trueba, Yolanda (Universidad Nacional del Litoral, 2019)
In the final years of the 19th century and the beginning of the 20th, the placement of children and young people with families different from the one of origin was invigorated. The objective of this paper is to rethink the link between servants and depositaries in the province of Buenos Aires. The article asks about the origin of the placements and the varied work arrangements that they entailed.  It is assumed that they were part of a paternalistic relationship that combined duties and obligations, united by a labor link. This task will be done through the documental funds of the Defensorías de Menores y Juzgados de Paz in the area studied.